2006
DOI: 10.1136/emj.2006.035071
|View full text |Cite
|
Sign up to set email alerts
|

A study of depression and anxiety among doctors working in emergency units in Denizli, Turkey

Abstract: Background: Major work has been carried out on the psychological well-being of emergency room doctors in the US, Canada and in other developed countries, but little has been published regarding the same in the countries in economic transition. Objective: To determine the level of, and the factors related to, depression and anxiety among doctors working in emergency units in Denizli, Turkey. Methods: This cross-sectional study was conducted in May 2004, using a sample of 192 doctors employed in emergency units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
65
2
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 22 publications
(28 reference statements)
12
65
2
8
Order By: Relevance
“…Therefore the pre -formed hypothesis, 'female medical professionals are more likely to experience burnout syndrome than males' is void; cannot be accepted. Current finding falls in line with the work of Erdur et al, (2006), who also could not establish a relationship between gender and burnout syndrome. Contrastingly other scholars have established causal relationships where female physicians were more burned out than their male counter parts (Embriaco et al, 2007).…”
Section: Discussion Of Findings Of the Validity Of The Pre -Establishsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore the pre -formed hypothesis, 'female medical professionals are more likely to experience burnout syndrome than males' is void; cannot be accepted. Current finding falls in line with the work of Erdur et al, (2006), who also could not establish a relationship between gender and burnout syndrome. Contrastingly other scholars have established causal relationships where female physicians were more burned out than their male counter parts (Embriaco et al, 2007).…”
Section: Discussion Of Findings Of the Validity Of The Pre -Establishsupporting
confidence: 87%
“…Contradictory findings indicate that there is no such established relationship between gender and the syndrome (Erdur et al, 2006). Higher levels of burned-out individuals were seen to be less frequently married or partnered and more often did not have children (Embriaco et al, 2007).…”
Section: Work Family Conflictmentioning
confidence: 95%
“…As stated earlier, the participants were university students, with a mean age of 22. The participants' level of depressive symptoms in this study were similar to those observed in previous studies that employed university student participants (Bayram & Bilgel, 2008;Bilican, 2013;Cam-Celikel & Erkorkmaz, 2008;Ceyhan et al, 2005;Hisli, 1989;Unsal & Ayranci, 2008), and adults (Erdur et al, 2006;Tekbas, Ceylan, Hamzaoglu, & Hasde, 2003). However, the findings may not be generalized to older people in Turkey.…”
Section: Discussionsupporting
confidence: 83%
“…In comparison, the prevalence of anxiety symptoms in the UK, Turkey and Saudi Arabia were reported to be 54%, 14.6% and 8.6%, respectively (Firth, 1987;Erdur et al, 2006;Niku, 2004).…”
Section: Discussionmentioning
confidence: 99%